Disrupted Resolution Mechanisms Favor Altered Phagocyte Responses in COVID-19. Issue 4 (9th July 2021) - Koenis, Duco Steven; Beegun, Issa; Jouvene, Charlotte Camille; Aguirre, Gabriel Amador; Souza, Patricia Regina; Gonzalez-Nunez, Maria; Ly, Lucy; Pistorius, Kimberly; Kocher, Hemant M.; Ricketts, William; Thomas, Gavin; Perretti, Mauro; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Resolution mechanisms are central in both the maintenance of homeostasis and the return to catabasis following tissue injury and infections. Among the proresolving mediators, the essential fatty acid-derived specialized proresolving lipid mediators (SPM) govern immune responses to limit disease severity. Notably, little is known about the relationship between the expression and activity of SPM pathways, circulating phagocyte function and disease severity in patients infected with the novel severe acute respiratory syndrome coronavirus 2 leading to coronavirus disease 2019 (COVID-19). Objective: Herein, we investigated the link between circulating SPM concentrations and phagocyte activation status and function in patients with COVID-19 (n=39) compared with healthy (n=12) and post-COVID-19 (n=8) volunteers. Methods and Results: Lipid mediator profiling demonstrated that plasma SPM concentrations were upregulated in patients with mild COVID-19 and are downregulated in those with severe disease. SPM concentrations were correlated with both circulating phagocyte activation status and function. Perturbations in plasma SPM concentrations and phagocyte activation were retained after the resolution of COVID-19 clinical symptoms. Treatment of patients with dexamethasone upregulated both the expression of SPM biosynthetic enzymes in circulating phagocytes and plasma concentration of these mediators. Notably, incubation of phagocytes from patients with COVID-19 with SPM rectified their phenotype and function. This included a downregulation in the expression of activation markers, a decrease in the tissue factor and inflammatory cytokine expression, and an upregulation of bacterial phagocytosis. Conclusions: The present findings suggest that downregulation of systemic SPM concentrations is linked with both increased disease severity and dysregulated phagocyte function. They also identify the upregulation of these mediators by dexamethasone as a potential host protective mechanism elicited by this drug in patients with COVID-19. Taken together, our findings elucidate a role for altered resolution mechanisms in the disruption of phagocyte responses and the propagation of systemic inflammation in COVID-19.